University Professors and the Production and Circulation of Knowledge: a Study of Argentine Universities - Riquelme, Graciela C.; Langer, Ariel A. (CIAN-Revista de Historia de las Universidades, 2013)
This article reviews the main dimensions of a research about the capacities of the teaching and researching groups of Argentinean universities regarding the social and productive demands. The project developed and extensive and deep consult to eighty groups of three universities: University of Buenos Aires, National University of Mar del Plata and the National University of Misiones. Through the analysis of the interviewees’ discourses we develop two research hypotheses about the transformation of the activities of the groups and about the new logics in the treatment of the social and productive demands.
Keywords: Argentina; university; research; teaching; social and productive demands